Multi-proxy climate and environmental records from a Holocene eutrophic mire, southern taiga subzone, West Siberia - Kurina, Irina V.; Veretennikova, Elena E.; Ilina, Anna A.; Egorova, Marina L.; Salisch, Lyudmila V.; Dolgin, Vladimir N.; Udaloi, Albert V.; Golovatskaya, Evgeniya A.; Dyukarev, Egor A.; Smirnov, Sergey V. (Boreas)
Palaeoenvironmental reconstructions from peat are strongly focused on ombrotrophic mires, but this study demonstrates that eutrophic mires can also be used. A multi-proxy approach was applied to a eutrophic mire on a floodplain terrace in the southern taiga of West Siberia.A multi-proxy approach was applied to a eutrophic mire on a floodplain terrace in the southern taiga of West Siberia. The results of the reconstructionwere considered in the wide geographic context of the surrounding regions, including Siberia and Central Asia.